Why Do People Buy iPhones? Unveiling the Role of Product Quality and Price Perception in Jakarta - Delicia, Putri; Rosalina, Sylvia Sari (Transpublika Publisher, 2025)
This research examines how the perceived quality and price of products influence the choices consumers make when purchasing iPhones in DKI Jakarta. Using a quantitative survey method, data were collected from iPhone users who had owned the device for at least one year. The examination, carried out using SPSS 26, comprised of tests on validity and reliability, as well as an analysis using multiple linear regression. The results indicate that the quality of the product has a significant impact on consumer purchasing choices. Consumers prioritize durability, technological innovation, and premium design, indicating that higher perceived quality increases the likelihood of purchase. However, price perception does not significantly impact purchasing decisions. Despite the iPhone’s higher price, consumers in Jakarta value symbolic status and brand prestige over cost considerations. High purchasing power, installment options, and strong marketing strategies contribute to reducing price sensitivity. In conclusion, product quality is a key factor in purchasing decisions, while price perception is not. Apple should continue enhancing product quality and brand loyalty to maintain its market position. Future research could explore other factors, such as brand trust or lifestyle, to gain deeper insights into consumer behavior.